Uncovering the Concept of Corporations’ Human Rights Performance - Brodersen, Mathias Elmark (2010)

(untitled)
This study investigates the institutional determinants of western corporations’ human rights performance, specifically focused on their operations in the developing world. With privileged access to data rating corporations on human rights performance, the present study reports a statistical analysis of the influence of institutional factors while controlling for industry and firm characteristics. Building on neo-institutional theory (DiMaggio and Powell, 1983; Meyer and Rowan, 1977), this study explores whether institutions such as regulation and normative pressure influence corporations’ human rights performance. As regulation directed towards preventing human rights infringements in corporations’ overseas operations is found to be largely absent, only normative pressure is included in the statistical test. The results suggest that firm size and the normative pressure for human rights in the corporations’ home country have significant influence on the community impact aspect of corporations’ human rights performance. Corporations operating in the US are found to have a lower performance compared to their counterparts in Western Europe, Australia and Canada. The “tenuous” relation to international human rights norms in the US is emphasised as central explanation for this. The control variables financial performance, risk and industry were found not to be significant predictors of the community impact aspect of corporations’ human rights performance. While the community aspect of human rights performance is the only aspect statistically explored, the findings nevertheless seem likely to hold for the supply chain management and employment practices aspects as well. Future research is needed to uncover these relationships. By being the first study solely dedicated to uncovering determinants of corporations’ human rights performance, this dissertation contributes to the development of a theoretical field dedicated to uncovering determinants of corporations’ human rights performance in respect to their operations in the developing world.